Influência da infecção por Trypanosoma evansi no metabolismo de ferro em ratos experimentalmente infectados - Silva, Cássia Bagolin da (2011)
Trypanosoma evansi is the causative agent of the disease known as Mal das cadeiras or Surra in horses. Has a wide geographical distribution and is commonly found parasitizing several species of domestic and wild animals. Anemia is a common feature and perhaps the most important in infections with T. evansi, however, the mechanisms by which it originates has not been fully elucidated. Considering that iron deficiency may play a crucial role in anemia caused by trypanosomiasis, due to their involvement in hematopoietic, the aim of this study was to evaluate the possible effects of experimental infection with Trypanosoma evansi in Wistar rats on the iron status and of its forms of storage and carting, and also storage in the bone marrow level, establishing a correlation with hematologic findings. To that end, 32 male Wistar rats were divided into four groups, two control groups (C5 and C30) composed by six non-inoculated animals and two test groups (T5 and T30) inoculated with T. evansi, with 10 animals in each group. Blood samples were collected at 5 days post-inoculation (C5 and T5) and 30 days post-inoculation (C30 and T30). Iron status was determined in serum using commercial kits of ferrozine and cromazurol iron, ferritin, transferrin and iron binding capacity. The transferrin saturation index was calculated from the results obtained. The bone marrow was also evaluated for the presence of iron, by the reaction of Pearls. It was observed that the levels of iron, cromazurol iron and total and latent iron binding capacity decreased significantly (P <0.05) at 5 and 30 days pi in animals in the infected group when compared to the control group. Since the levels of transferrin and ferritin increased (P <0.05). The transferrin saturation index increased to 5 days pi, observing the decline of the index at 30 days pi. Infected animals showed a greater tendency to accumulate iron in bone marrow. Infection with T. evansi in rats caused anemia and changes in iron metabolism, as those related to the peaks of parasitemia. These results suggest that changes in iron metabolism may be related to body's immune response to infection and anemic status of infected animals.